Zoonotic Bartonella species in Eurasian wolves and other free‐ranging wild mammals from Italy. (29th March 2021) - Greco, Grazia; Zarea, Aya Attia Koraney; Sgroi, Giovanni; Tempesta, Maria; D'Alessio, Nicola; Lanave, Gianvito; Bezerra‐Santos, Marcos Antônio; Iatta, Roberta; Veneziano, Vincenzo; Otranto, Domenico; Chomel, Bruno
Abstract: Bartonellae are emerging vector‐borne pathogens infecting humans, domestic mammals and wildlife. Ninety‐seven red foxes ( Vulpes vulpes ), 8 European badgers ( Meles meles ), 6 Eurasian wolves ( Canis lupus ), 6 European hedgehogs ( Erinaceus europaeus ), 3 beech martens ( Martes foina ) and 2 roe deer ( Capreolus capreolus ) from Italian Nature Conservatory Parks were investigated for Bartonella infection. Several Bartonella species (9.84%; 95% CI: 4.55–15.12), including zoonotic ones, were molecularly detected among wolves (83.3%; 95% CI: 51–100.00), foxes (4.12%; 95% CI: 0.17–8.08), hedgehogs (33.33%; 95% CI: 0.00–71.05) and a roe deer. Bartonella rochalimae was the most common Bartonella species (i.e. in 4 foxes and 2 wolves) detected. Candidatus B. merieuxii and B. vinsonii subsp. berkhoffii were identified for the first time in wolves. Furthermore, Bartonella schoenbuchensis was identified in a roe deer and a new clone with phylogenetic proximity to B. clarridgeiae was detected in European hedgehogs. Zoonotic and other Bartonella species were significantly more frequent in Eurasian wolves ( p  < .0001), than in other free‐ranging wild mammals, representing a potential reservoir for infection in humans and domestic animals.